Gender stereotypical toy preferences in children 3-5 - (:unkn) unknown (IGI Global, 2018)
Gender socialisation is the process through which society teaches children what it means to be male or female. While gender socialisation itself is a cross-cultural phenomenon, there are differences in the way that the process manifests itself cross-culturally. This is, in part, due to differences in the perceived roles of males and females across societies. Once the sex of a child is known, be that before or after birth, the process of gender socialisation begins. Parents generally prefer that their children adhere to traditional gender-roles, and are concerned when they do not. Rigid adherence to stereotypical gender roles can have negative consequences in childhood and beyond, as these stereotypes can limit children's educational and occupational aspirations, perceived academic competency, emotional expression, and social development. The impact of culture and parental influence in adherence to stereotypical gender roles is discussed via toy preferences and play. © 2018, IGI Global. All rights reserved.